CCL5 mediates breast cancer metastasis and prognosis through CCR5/Treg cells - Qiu, Juanjuan; Xu, Li; Zeng, Xiaohong; Wu, Hao; Liang, Faqing; Lv, Qing; Du, Zhenggui (Frontiers in Oncology, 2022)
Background and aims: CCL5 is considered to contribute to the biological function of a variety of cancer types, but its specific mechanism is still unclear. This study aimed to reveal the mechanism of CCL5 in the invasion, metastasis, and prognosis of breast cancer. Methods: The expression of CCL5 in tumor tissue and serum was measured with a Luminex protein detection kit, and the correlation between CCL5 and clinical parameters was evaluated. Kaplan–Meier analysis was used to analyze the effect of CCL5 on the prognosis of breast cancer patients. Protein interaction network analysis and gene coexpression were used to determine the receptor that has the strongest interaction with CCL5. Enrichment analysis was used to study the possible pathway by which CCL5 affects breast cancer progression. We used immunofluorescence staining and flow cytometry to estimate the fraction of immunity-related components in the tumor microenvironment. Results: The expression level of CCL5 in breast cancer patients was positively correlated with the degree of axillary lymph node metastasis; CCL5 in tumor tissue was correlated with estrogen receptor status (P = 0.034), progesterone receptor (P = 0.009), nuclear grade (P = 0.013), clinical stage (P < 0.001) and molecular subtype (P = 0.024) in breast cancer patients. Breast cancer patients with high CCL5 expression had worse disease-free survival (P = 0.031) and breast cancer-specific survival (P = 0.043); however, CCL5 had no effect on overall survival (P = 0.077). CCL5 affected tumor progression through CCR5, and the T-cell-related immune pathway may be the main pathway; the CD4+/CD8+, CCR5+/CD4+ and Treg/CCR5+ cell ratios were significantly increased in the lymph node metastasis group. Conclusion: CCL5 affects the Treg/CD4+CCR5+ cell ratio in breast cancer patients through CCR5, thus affecting breast cancer metastasis and prognosis.